Significant Electromechanical Characteristic Enhancement of Coaxial Electrospinning Core–Shell Fibers - Duc-Nam Nguyen (MDPI, 2022)
Electrospinning is a low-cost and straightforward method for producing various types of polymers in micro/nanofiber form. Among the various types of polymers, electrospun piezoelectric polymers have many potential applications. In this study, a new type of functional microfiber composed of poly(γ-benzyl-α,L-glutamate) (PBLG) and poly(vinylidene fluoride) (PVDF) with significantly enhanced electromechanical properties has been reported. Recently reported electrospun PBLG fibers exhibit polarity along the axial direction, while electrospun PVDF fibers have the highest net dipole moment in the transverse direction. Hence, a combination of PBLG and PVDF as a core–shell structure has been investigated in the present work. On polarization under a high voltage, enhancement in the net dipole moment in each material and the intramolecular conformation was observed. The piezoelectric coefficient of the electrospun PBLG/PVDF core–shell fibers was measured to be up to 68 pC N−1 (d33), and the voltage generation under longitudinal extension was 400 mVpp (peak-to-peak) at a frequency of 60 Hz, which is better than that of the electrospun homopolymer fibers. Such new types of functional materials can be used in various applications, such as sensors, actuators, smart materials, implantable biosensors, biomedical engineering devices, and energy harvesting devices